Pengetahuan dan Akses Informasi Ibu Hamil tentang Efektifitas Minuman Seduhan Jahe terhadap Pengurangan Emesis Gravidarum - Tiwi, Laida Sanilpa; Perwitasari, Tuhu (Universitas Baiturrahim, 2024)
Emesis gravidarum is a normal symptom and is often found in the first trimester of pregnancy. Most pregnant women experience nausea and vomiting at various levels so that it can occur at any time, especially in the morning. Emesis gravidarum can be treated non-pharmacologically, one of which is using ginger infusion. The efficacy of ginger as an anti-vomiting agent is considered to have milder side effects than anti-vomiting drugs. This study aims to determine the knowledge and access to information of pregnant women in reducing emesis gravidarum by drinking ginger infusion. The study was conducted on November 4, 2022-June 20, 2023. The type of research used is descriptive with a cross-sectional approach. The population in this study was 25 pregnant women with sampling carried out by total sampling, namely 25 pregnant women. The data collection technique used a closed questionnaire with 10 multiple-choice questions and a checklist by conducting validity and reliability tests on the questionnaire. Based on the results of the study, it is known that out of 25 respondents, most of the knowledge is sufficient, namely 16 (64%), how to overcome emesis gravidarum by drinking ginger infusion as much as 13 (52%) with the effectiveness of ginger infusion on reducing emesis gravidarum reduced by 11 pregnant women (84.6%), and respondents obtained access to information about ginger infusion from friends or neighbors and family as much as 10 (40%). Therefore, it is hoped that midwives can introduce this ginger infusion so that pregnant women can get accurate information, both on how to make it, and the right dosage for pregnant women in reducing emesis gravidarum.